Effects of Different Heat Processing on Molecular Weight and Allergenicity Profile of White Shrimp (Litopenaeus vannamei) and Mud Crab (Scylla serrata) from Indonesian Waters - Afif Arwani; Nurheni Sri Palupi; Puspo Edi Giriwono (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2022)
Shrimp and crab are fishery products with high nutritional value, especially as protein sources. However, they belong to the crustacean group known to cause many allergies in Southeast Asian countries. Not only affecting the nutritional composition, processing also has the potential in reducing the allergenicity of a food ingredient. This study aims to analyze the effects of various heat processing on nutrient composition, soluble protein content, protein molecular weight profile, and allergenicity of white shrimp and mud crab. The processing was carried out by boiling, frying, and autoclaving. Changes in macronutrient content were determined using proximate analysis. Soluble protein content was analyzed using the Bradford method, while molecular weight and allergenicity profiles were analyzed using SDS-PAGE electrophoresis and ELISA techniques. Results showed that processing treatment could significantly reduce protein solubility. SDS-PAGE profile showed that heating shrimp and crab using autoclave at 121.1 oC and pressure of 0.2 MPa for 10 min was able to remove protein bands of 35-38 kDa, which were suspected as the allergen bands. However, boiling (100 oC for 10 min) and deep frying in palm oil (160 oC for 10 min) treatments of the samples gave stronger 35-38 kDa bands intensity than the unprocessed sample. Autoclaving was able to significantly reduce IgE reactivity to shrimp extract better than the boiling and frying process. In contrast, IgE reactivity of crab extract was increased by heat processing especially frying. Thus, autoclaving can be used in the white shrimp processing to produce hypoallergenic food.